Harnessing mesenchymal stromal cells for liver disease therapy: from mechanistic discoveries to clinical breakthroughs - Huang, Yiting; Cheng, Ruogu; Wang, Guaijuan; Xu, Zihan; Liu, Shuping; Wan, Yantong; Hou, Xinjiang; Wang, Jieyan (Frontiers in Medicine, 2026)
Mesenchymal stromal cells (MSCs) demonstrate significant potential in liver tissue regeneration and disease treatment due to their unique immunomodulatory properties, multipotent differentiation capabilities, and paracrine functions. This article provides a systematic review of MSCs’ biological characteristics and mechanistic roles in liver regeneration and summarizes recent clinical advancements and future challenges. Evidence reveals that MSCs exert therapeutic effects by secreting bioactive mediators—including hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), and extracellular vesicles (EVs)—to inhibit hepatic stellate cell (HSCs) activation, degrade fibrotic extracellular matrix(ECM), and stimulate endogenous hepatocyte proliferation coupled with neovascularization. Their immunomodulatory functions reshape the hepatic immune microenvironment through inducing macrophage polarization toward the anti-inflammatory M2 phenotype, suppressing T-cell activation, and modulating the Th17/Treg balance. Preclinical studies confirm that MSCs effectively restore liver function and reverse fibrosis in diverse liver injury models. Preliminary clinical trials further validate their safety and efficacy, with allogeneic MSC infusion demonstrating survival benefits in end-stage liver disease patients. However, heterogeneity in cell sources, low homing efficiency, and lack of standardized preparation protocols remain major bottlenecks for clinical application. Emerging strategies integrating CRISPR-based gene editing, engineered exosome delivery platforms, and biomaterial-guided localization are imperative to refine targeting specificity and therapeutic precision. This review provides theoretical support and innovative directions for the translational application of MSCs in liver disease therapy.